Strategi Pengembangan Bisnis Jasa Surveyor Independen Pada Unit Bisnis Batubara PT XYZ: Business Development Strategy of Independent Surveyor Service on Coal Business Unit PT XYZ - Fajar Sidiq; Raden Dikky Indrawan Indrawan; Rokhani Hasbullah (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The market for coal exports from Indonesia expands annually; therefore, the government must issue a regulation to designate local technical verifier surveyors to inspect coal exports in order to manage the production and sale of coal. PT XYZ as a foreign surveyor service company needs to have the proper alternative strategy to respond to these government regulations. Purpose: The purpose of this study was to analyze the external and internal factors that affect PT XYZ’s business, formulate strategy alternatives, and determine the proper business strategy for coal unit business of PT XYZ. Design/methodology/approach: The analytical tools used for the macro and industry external environments were PESTEL and Porter’s Five Forces analysis, while the internal environment analysis used VRIO. Strategy alternatives were formulated by SWOT-TOWS analysis, and determination of strategy priority used hybrid AHP-SWOT (A’WOT) analysis. Findings/Result: The results showed that the opportunity factor is at the top of the list. At the sub-factor level, the external factor as the biggest opportunity is that other countries’ dependence on Indonesian coal is very high, and the biggest threat is that the government is still closing operating permits for foreign surveyors, while the internal factor as the biggest strength is accuracy and timely survey reports and laboratory results, and the biggest weakness is the cooperation contract with customers and local surveyors. Conclusion: The study concluded that the main priority of the 13 structured alternative strategies that can be implemented by PT XYZ is the WO2 strategy to increase the volume of work, which is a long-term cooperation contract other than spot-order work with customers.Originality/value (State of the art): The selection of PT XYZ as a foreign independent surveyor service company that operating in Indonesia in this study is different and has not been found in previous studies. Keywords: A’WOT, business strategy, coal, independent surveyor, quantity and quality inspection